Testing the Arabic short form versions of the Parental-Caregivers Perceptions Questionnaire and the Family Impact Scale in Oman - I.A. Al-Riyami; W.M. Thomson; L.S. Al-Harthi (Saudi Dental Journal)
Short form versions of the Parental-Caregivers Perception Questionnaire (P-CPQ) and Family Impact Scale (FIS) have been developed for use as measures of oral health-related quality of life in dental research. Objectives: (1) To translate the original English short form versions of the P-CPQ and FIS and examine their validity, and (2) to describe the impact of early childhood caries on oral health-related quality of life in young Omani children and their families. Methods: Parents/caregivers of children awaiting treatment for early childhood caries completed the P-CPQ and FIS at the Military Dental Center in Oman. Data were obtained from 191 families (representing a 94.1% participation rate). A global Oral Health Quality of Life (OHRQoL) item was used concurrently to examine the scales’ validity. Results: The cross-sectional concurrent validity of the short form version of the P-CPQ was apparent in the significant gradient across the response categories of the global OHRQoL item, but the FIS short form version did not perform as well. Conclusion: The P-CPQ appears to be valid, but further investigation of the FIS is required, along with examination of the scales’ responsiveness to change. Keywords: Child, Oral health, Quality of life